Financial development and renewable energy consumption in Nigeria - Stephen Kelechi Dimnwobi; Chekwube V. Madichie; Chukwunonso Ekesiobi; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
Financial sector performance is increasingly linked with the transition to renewable energy in the sustainability discourse of developing economies. This paper examines the nexus and implication (s) of financial development on renewable energy consumption in Nigeria (the largest and most p opulous economy in Africa). Specifically, this study utilised the broad-based financial developm ent index data to effectively address the multidimensional nature of financial development and th e portion of renewable energy in total energy consumption as key variables, while other relevant pieces of information (growth rate of per capita GDP, foreign direct investment and consumer pri ce index) were incorporated. The study employed a blend of the ADF test and Zivot-Andrew test to ascertain stationarity properties as well as the likelihood of structural breaks, while the ARDL was utilized to determine the long-run relationship(s) using data from 1981 to 2019. The study estimation finds, among other things, that financial development is critical for renewable energy consumption in Nigeria and recommends policies to promote better outcomes for the financial and energy sectors, respectively.
Keywords: 330; Financial development; Renewable energy consumption; Nigeria